Colloidal material for hot-state repair of high-zirconium brick of electronic glass kiln and preparation method of colloidal material

By using gelatinous repair materials made of zirconium dioxide and other materials in glass kilns, the problem of repairing high zirconium bricks at high temperatures is solved, efficient repair and stability of the kiln is achieved, and the service life of the kiln is extended. Reduced production costs.

CN119306494APending Publication Date: 2025-01-14SICHUAN SHUWANG CHENSHENG NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411485509.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The prior art is difficult to quickly repair and protect the high zirconium bricks in glass kilns under high temperature environments, resulting in limited kiln stability and service life. Traditional repair methods are time-consuming and costly, which affects production efficiency.

Method used

Develop a gel-like material including zirconium dioxide, single crystal powder alumina, silicon micropowder, boron compounds, rare earth oxides, silicon carbide and phosphate binder to form high-temperature curing and corrosion resistance by heating treatment. Repairing materials can quickly cure at high temperatures and closely combine with the matrix material.

Benefits of technology

It realizes rapid repair of high zirconium bricks in high temperature environments, extends the service life of the kiln, improves production efficiency, reduces production costs, and significantly improves the maintenance efficiency and operating stability of the kiln.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098613160000071
    Figure BDA0005098613160000071
Patent Text Reader

Abstract

The invention discloses a colloidal material for hot-state repair of a high-zirconium brick of an electronic glass kiln and a preparation method of the colloidal material, and relates to the technical field of glass production. According to the technical scheme, the high-temperature-resistant zirconium oxide ceramic comprises the following components in percentage by mass: 50-70% of zirconium dioxide, 10-20% of single-crystal powdery aluminum oxide, 5-15% of silica powder, 2-8% of a boron compound, 1-4% of rare earth oxide, 0-3% of silicon carbide, 0-5% of nano aluminum oxide and 5-15% of a phosphate binder. The colloidal material disclosed by the invention can be rapidly cured in a high-temperature environment, is tightly combined with a matrix material, has excellent molten glass corrosion resistance and thermal stability, and can rapidly recover the use performance of a kiln, prolong the service life of the kiln and improve the production efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glass production, and in particular to a colloidal material for hot repairing of high-zirconium bricks in an electronic glass furnace and a preparation method thereof. Background Art

[0002] In the production process of TFT electronic glass substrates, the kiln is one of the key equipment. The high temperature environment inside the kiln during the production process places extremely high demands on the refractory materials of the kiln. High zirconium bricks are used in key parts of glass kilns due to their excellent high temperature resistance and corrosion resistance, and they are often in direct contact with molten glass. However, long-term high-temperature operation and complex chemical environment will still cause damage such as erosion, cracking and even explosion of high zirconium bricks, affecting the stability and service life of the kiln, and thus affecting product output and quality. Traditional repair methods often require shutdown and cold repair, which is not only time-consuming and costly, but also seriously affects the production efficiency of the enterprise. Therefore, it is particularly important to develop a high-performance repair material that can directly repair high zirconium bricks in a hot state. Summary of the invention

[0003] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art and provide a colloidal material for hot repair of high-zirconium bricks in an electronic glass kiln and a preparation method thereof. The colloidal material can be quickly solidified in a high-temperature environment, tightly combined with the matrix material and has excellent resistance to glass liquid corrosion and thermal stability, and can quickly restore the kiln's performance, extend the service life of the kiln, and improve production efficiency.

[0004] The technical solution of the present invention is:

[0005] On the one hand, the present invention provides a colloidal material for hot repair of high-zirconium bricks in an electronic glass kiln, comprising the following components in percentage by mass: 50-70% zirconium dioxide, 10-20% single crystal powdered alumina, 5-15% silicon powder, 2-8% boron compound, 1-4% rare earth oxide, 0-3% silicon carbide, 0-5% nano alumina, and 5-15% phosphate binder.

[0006] Preferably, the boron compound is boric acid or boron oxide.

[0007] Preferably, the rare earth oxide is yttrium oxide (Y2O3).

[0008] Preferably, the phosphate binder is magnesium dihydrogen phosphate (Mg(H2PO4)2).

[0009] On the other hand, the present invention provides a method for preparing the colloidal material for hot repairing of high-zirconium bricks in the electronic glass furnace, comprising the following steps:

[0010] S1 raw material pretreatment;

[0011] S2 mixes the raw materials uniformly to obtain a mixed material;

[0012] S3 heats the mixture to obtain a gelatinous material.

[0013] Preferably, in step S1, the specific operation of raw material pretreatment is: grinding each raw material except nano-alumina separately, and sieving through a sieve.

[0014] Preferably, in step S1, the particle sizes of the raw materials after screening are 100-300 mesh for zirconium dioxide, 200-400 mesh for single crystal powdered alumina, 300-500 mesh for silicon powder, 200-300 mesh for boron compound, 150-300 mesh for rare earth oxide, 150-300 mesh for silicon carbide, and 200-300 mesh for phosphate binder.

[0015] Preferably, in step S2, the raw materials except the phosphate binder are mixed and the phosphate binder is added during the mixing process, and stirred until a uniform mixture is formed.

[0016] Preferably, in step S3, the mixture is heated at 200-500° C. until it forms a gelatinous material.

[0017] In the colloidal material of the present invention:

[0018] Zirconium dioxide: As the main component, it provides excellent high temperature resistance and corrosion resistance;

[0019] Single crystal powdered alumina: enhances the hardness and wear resistance of the material;

[0020] Silica powder: improve the fluidity and adhesion of materials;

[0021] Boric acid and borates: as flux and binder, they adjust the fluidity of the material and make the mixture into a colloid after heating, which is convenient for use. They can also promote the rapid solidification of the material at high temperature and the close combination with the base material;

[0022] Rare earth oxides: improve the thermal stability and corrosion resistance of materials, and can also promote the polycondensation reaction of phosphate binders and the reaction with other ingredients, accelerating the curing speed;

[0023] Silicon carbide: can improve the wear resistance and resistance to glass liquid erosion of the repair material, and is suitable for harsher glass liquid flow environments;

[0024] Nano-alumina: It can increase the content of single-crystal powdered alumina, improve the wear resistance and erosion resistance of the repair material, and is suitable for harsher glass liquid flow environments; it can also improve the density and strength of the repair material, and further enhance its high temperature resistance and glass liquid erosion resistance;

[0025] Phosphate binder: As a binder, it makes the mixture form a colloidal substance after heating, adjusts the fluidity and curing properties of the material, promotes the rapid curing of the material at high temperature and the close bonding with the base material.

[0026] Phosphate binders are usually liquid or powdery at room temperature, with certain fluidity and operability. Under high temperature conditions, they undergo a series of complex chemical reactions to solidify and firmly bond other components together:

[0027] 1) Chemical reaction during high temperature curing

[0028] Dehydration reaction

[0029] When the temperature rises, the water in the phosphate binder begins to evaporate first. This process can remove the free water in the phosphate binder and create conditions for subsequent chemical reactions.

[0030] Polycondensation

[0031] When the temperature rises further, condensation reactions will occur between phosphate molecules. For example, orthophosphate will gradually transform into polyphosphate at high temperature, and the phosphate ions will dehydrate and condense to form a longer chain or network structure, which can increase the strength and stability of the phosphate binder.

[0032] The role of phosphate binder and other ingredients in the material:

[0033] Zirconium dioxide, single crystal powdered alumina, silicon powder, nano-alumina and other components will also react with phosphate binders at high temperatures. For zirconium dioxide, the zirconium ions (Zr 4+ ) and the phosphate ion (PO4 3- ) to form zirconium phosphate compounds, which enhances the bonding force between the phosphate binder and the zirconium dioxide particles. Similarly, single crystal powdered alumina and nano alumina can react with the phosphate binder to form aluminum phosphates, improving the overall strength and high temperature resistance of the material. Silicon powder can react with phosphates at high temperatures to form silicon phosphates, further enhancing the structural stability of the material.

[0034] Role of rare earth oxides: Rare earth oxides also play an important role in the high-temperature curing process. They can act as catalysts to promote the polycondensation reaction of phosphate binders and reactions with other components, thereby accelerating the curing speed.

[0035] 2) Performance of the gel material after high temperature curing

[0036] After high temperature curing, the phosphate binder firmly bonds the other components together to form a whole with high strength and stability. This material can withstand harsh environments such as high temperature, high pressure and chemical corrosion, and is suitable for high-demand applications such as glass kilns.

[0037] High temperature resistance: Since the phosphate binder forms a stable structure at high temperatures and interacts with other high temperature resistant components, the cured material has excellent high temperature resistance. Moreover, it can still maintain the stability of its physical and chemical properties at high temperatures without softening, deformation or decomposition.

[0038] Chemical stability: The compounds formed by phosphate binder and other components have high chemical stability and can prevent the erosion of materials by corrosive media such as molten glass and furnace gas.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] The colloidal material of the present invention can be quickly solidified in a high temperature environment, effectively fill the cracks and defects of high zirconium bricks, improve the overall stability and service life of the kiln, solve the problem of difficult hot repair in the prior art, and realize the direct repair of high zirconium bricks in the hot state of the glass kiln, avoiding the production interruption and cost increase caused by traditional cold repair. This technological innovation significantly improves the maintenance efficiency and operation stability of the kiln. The colloidal material of the present invention has excellent thermal stability, high temperature resistance, resistance to glass liquid corrosion and low thermal expansion coefficient, can be quickly solidified in a high temperature environment and tightly combined with the base material, the repair process does not need to interrupt the kiln production, reduces production costs and improves production efficiency. DETAILED DESCRIPTION

[0041] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.

[0042] Example 1

[0043] The colloidal material for hot repair of high-zirconium bricks for electronic glass furnaces in this embodiment includes the following components in percentage by mass: 63% zirconium dioxide, 13% single-crystal powdered alumina, 8% silicon powder, 5% boric acid, 3% rare earth oxide, and 8% magnesium dihydrogen phosphate.

[0044] Example 2

[0045] The colloidal material for hot repair of high-zirconium bricks for electronic glass furnaces in this embodiment includes the following components in percentage by mass: 61.74% zirconium dioxide, 12.74% single-crystalline powdered aluminum oxide, 7.84% silicon powder, 4.9% boric acid, 2.94% rare earth oxide, 7.84% magnesium dihydrogen phosphate, and 2% silicon carbide.

[0046] Example 3

[0047] The colloidal material for hot repair of high-zirconium bricks for electronic glass furnaces in this embodiment includes the following components in percentage by mass: 61.74% zirconium dioxide, 12.74% single-crystalline powdered aluminum oxide, 7.84% silicon powder, 4.9% boric acid, 2.94% rare earth oxide, 7.84% magnesium dihydrogen phosphate, and 2% nano-alumina.

[0048] Example 4

[0049] The colloidal material for hot repair of high-zirconium bricks in the electronic glass kiln of this embodiment includes the following components in percentage by mass: 50% zirconium dioxide, 16.15% single-crystalline powdered aluminum oxide, 9.95% silicon powder, 6.22% boric acid, 3.73% rare earth oxide, 9.95% magnesium dihydrogen phosphate, 2% silicon carbide, and 2% nano-alumina.

[0050] Example 5

[0051] The colloidal material for hot repair of high-zirconium bricks for electronic glass furnaces in this embodiment includes the following components in percentage by mass: 70% zirconium dioxide, 9.14% single-crystalline powdered aluminum oxide, 5.62% silicon powder, 3.51% boron oxide, 2.11% rare earth oxide, 5.62% magnesium dihydrogen phosphate, 2% silicon carbide, and 2% nano-alumina.

[0052] The preparation method of the colloidal material for hot repairing of high zirconium bricks for electronic glass furnaces of Examples 1-5 comprises the following steps:

[0053] S1: Grind the raw materials except nano-alumina separately, and sieve them through a sieve to the required particle size: zirconium dioxide 200 mesh, single crystal powdered alumina 300 mesh, silicon powder 400 mesh, boron compound 250 mesh, rare earth oxide 200 mesh, silicon carbide 200 mesh, phosphate binder 250 mesh;

[0054] S2: mixing the raw materials except magnesium dihydrogen phosphate and gradually adding magnesium dihydrogen phosphate during the mixing process, and stirring thoroughly until the mixture forms a uniform mixture;

[0055] S3: heating the mixture at 300°C until it forms a gel-like material.

[0056] When in use, the colloidal material prepared in Examples 1-5 is transferred to an electronic glass kiln and directly applied to cracks or defects in high-zirconium bricks. The high temperature environment in the kiln (usually temperature > 1500°C) is utilized to allow the colloidal material to solidify quickly and bond tightly with the base material, thereby achieving the purpose of hot repairing high-zirconium bricks.

[0057] Comparative Example 1

[0058] Comparative Example 1 uses the glass kiln refractory mud product of Foshan Shengyuan Refractory Insulation Materials Co., Ltd. as the high zirconium brick repair material.

[0059] The patching process is as follows:

[0060] (1) Stop the production of the electronic glass furnace and wait for the furnace to cool to room temperature;

[0061] (2) Clean the impurities and damaged parts on the surface of high zirconium bricks to ensure that the repair area is clean and free of oil;

[0062] (3) Use glass furnace refractory mud products for repair, apply it to the damaged area, and compact it with your hands or tools to ensure that it is in close contact with the base material;

[0063] (4) Wait for the refractory mud to dry and solidify naturally;

[0064] (5) Restart the kiln and raise the temperature to 1600°C at a rate of 50°C / h to avoid cracking in the repaired area due to excessive thermal stress.

[0065] Comparative Example 2

[0066] The corundum composite cast hot repair material product (powder) of Zhengzhou Huicheng Refractory Materials Co., Ltd. is used as the high zirconium brick repair material.

[0067] Patching process:

[0068] Repair operations are carried out in accordance with the requirements of the material specifications. There is no need to stop the kiln production. High-zirconium brick repairs are carried out directly in a hot state. The damaged area is determined using a kiln endoscope, and the corundum composite cast hot repair material mixed with high-purity oxygen is sprayed on the damaged area using a high-temperature resistant spraying device.

[0069] Comparative Example 3

[0070] The colloidal material for hot repair of high-zirconium bricks for electronic glass furnaces in Comparative Example 3 includes the following components in percentage by mass: 64.95% zirconium dioxide, 13.4% single-crystalline powdered aluminum oxide, 8.25% silicon powder, 5.15% boric acid, and 8.25% magnesium dihydrogen phosphate.

[0071] Comparative Example 4

[0072] The colloidal material for hot repair of high-zirconium bricks for electronic glass furnaces in Comparative Example 4 includes the following components in percentage by mass: 68.48% zirconium dioxide, 14.13% single-crystalline powdered aluminum oxide, 5.43% boric acid, 8.7% rare earth oxide, and 3.26% magnesium dihydrogen phosphate.

[0073] Comparative Example 5

[0074] The colloidal material for hot repair of high-zirconium bricks for electronic glass furnaces in Comparative Example 5 includes the following components in percentage by mass: 66.32% zirconium dioxide, 13.68% single-crystal powdered aluminum oxide, 8.42% silicon powder, 3.16% rare earth oxide, and 8.42% magnesium dihydrogen phosphate.

[0075] The performance tests were conducted on the repair materials of Examples 1-5 and Comparative Examples 1-5 and the repaired high zirconium bricks, and the test methods were as follows:

[0076] Glass liquid erosion resistance: Process the high zirconium brick into 30 small high zirconium bricks with a size of 5cm×5cm×5cm. According to the repair materials and repair methods in each embodiment and comparative example, a 0.5cm thick corresponding repair material is applied around each high zirconium brick. Three pieces are made for each embodiment and comparative example. After completion, the corresponding size is recorded. Then the high zirconium brick sample is placed in a platinum crucible filled with the same weight of broken glass, and the platinum crucible is placed in a high-temperature furnace. The temperature is set to 1650℃ and kept warm for 24 hours; after the insulation is completed, it is cooled to room temperature with the furnace. Take out the high zirconium brick sample, measure and record the size of the sample after erosion, calculate the erosion depth according to the change in sample size and take the average value.

[0077] Thermal expansion coefficient: The repair materials of each embodiment and comparative example were made into three cubes of the same size of 5 cm×5 cm×5 cm, and the thermal expansion coefficient of the samples was tested using the standard thermal expansion coefficient test method (GB / T 7320-2018 Refractory Thermal Expansion Test Method), and the average value was taken.

[0078] Volume resistivity: The repair materials of each embodiment and comparative example were made into three rectangular blocks of the same size of 10 cm × 10 cm × 2 cm, and the standard volume resistivity test method (EN IEC 62631-3-4-2019 Dielectric and resistive properties of solid insulating materials Part 3-4: Determination of resistance characteristics (DC method) Volume resistance and volume resistivity at high temperatures) was used to test the volume resistivity of the samples at 1650°C and 100 Hz frequency, and the average value was taken.

[0079] The performance test results of the repair materials of Examples 1-5 and Comparative Examples 1-5 and the repaired high-zirconium bricks are shown in Table 1:

[0080] Table 1 Performance test results of the repair materials of Example 1 and Comparative Examples 1-5 and the repaired high zirconium bricks

[0081]

[0082] It can be seen from the repaired high zirconium brick samples and the data in Table 1:

[0083] The surface of the high-zirconium bricks after repair in Example 1 and Example 4-5 is smooth, without obvious cracks or defects. The thermal expansion coefficient of the repairing materials used in Test Example 1 and Example 4-5 is small, and there is no cracking or falling off due to thermal stress. The high-zirconium bricks after repair in Example 1 and Example 4-5 show good resistance to glass liquid erosion and thermal stability in the glass production process, effectively extending the service life of the kiln. And by comparing with Comparative Examples 1-2, it can be seen that Example 1 and Example 4-5 are superior to other repair materials on the market in terms of glass liquid erosion rate, thermal expansion coefficient and volume resistivity.

[0084] Example 2 adds silicon carbide components on the basis of Example 1. Compared with Example 1, Example 2 is superior to Example 1 in terms of glass liquid erosion rate, thermal expansion coefficient and volume resistivity. This is because the added silicon carbide can improve the wear resistance and erosion resistance of the repair material, and is suitable for a more severe glass liquid flow environment. Silicon carbide can also solve the defects in the material (pores and microcracks), which will form local non-uniform structures and stress concentration areas in the material. For example, in a high-temperature oxygen environment, carbon on the surface of silicon carbide reacts with oxygen to generate carbon dioxide, while silicon reacts with oxygen to generate silicon dioxide. The generation of silicon dioxide can fill a part of the pores and microcracks, making the structure of the material more compact, and also changes the electrical properties of the material, affecting the transmission and concentration of carriers, reducing the scattering and capture effects of defects on carriers, thereby reducing the concentration of carriers (such as electrons, holes, etc.) in the material. A decrease in carrier concentration will lead to a decrease in the conductivity of the material, thereby increasing the volume resistivity; and the thermal expansion coefficient of silicon carbide is usually lower than that of high zirconium brick materials. After adding silicon carbide to the repair material, the silicon carbide particles can offset the thermal expansion of the repair material to a certain extent, thereby reducing the overall thermal expansion coefficient.

[0085] Example 3 adds nano-alumina on the basis of Example 1. Compared with Example 1, Example 3 is superior to Example 1 in terms of glass liquid erosion rate, thermal expansion coefficient and volume resistivity. This is because the added nano-alumina can increase the content of alumina, improve the wear resistance and erosion resistance of the repair material, and improve the density and strength of the repair material, further improving its high temperature resistance and glass liquid erosion resistance. The addition of nano-alumina will also increase the number of grain boundaries and interface area in the repair material. At these grain boundaries and interfaces, carriers (such as electrons, holes, etc.) will be scattered, resulting in a decrease in the mobility of carriers, thereby reducing the conductivity of the material and increasing the volume resistivity. Nano-alumina particles are mainly distributed at the grain boundaries of the repair material, and play a pinning role on the grain boundaries. This pinning effect can limit the thermal motion of the material, making it difficult for the material to expand when heated, thereby reducing the thermal expansion coefficient.

[0086] The repair material used in Comparative Example 1 is the commonly used cold repair refractory mud on the market. The repair process requires the kiln production to be interrupted, resulting in reduced production efficiency and increased costs. Refractory mud has a large thermal expansion coefficient at high temperatures and is prone to cracking and falling off when the kiln temperature fluctuates greatly. In addition, refractory mud has poor wear resistance and erosion resistance, and requires frequent repairs after long-term use.

[0087] The repair material used in Comparative Example 2 is a hot repair material for kilns made of high-zirconium bricks on the market. It has better effect than the repair material in Comparative Example 1, and the repair process is relatively simple without interrupting kiln production. However, it has poor wear resistance and resistance to erosion by molten glass, and a large thermal expansion coefficient. It is also prone to cracking and falling off when the kiln temperature fluctuates greatly. Moreover, the hot repair material is in the form of powder and requires pure oxygen as a combustion aid to melt it. It cannot repair larger defects in the kiln, vertical kiln walls, kiln crowns, and other locations.

[0088] No rare earth oxide is added to the colloidal material of Comparative Example 3. Compared with Example 1, Comparative Example 3 is inferior to Example 1 in terms of glass liquid erosion rate, thermal expansion coefficient and volume resistivity. This is because rare earth oxide can enhance the material's resistance to glass liquid erosion, and can also inhibit the growth of grains and the migration of grain boundaries in the material to a certain extent, making the material structure more compact and stable, which helps to stabilize the thermal expansion coefficient. When rare earth oxides are not added, the structural stability of the material will be affected, and the stability of the thermal expansion coefficient will deteriorate when the temperature changes, resulting in greater stress on high zirconium bricks due to temperature changes during kiln operation, increasing the possibility of cracking, peeling and other problems in the brick body. The special electronic structure of rare earth oxides will affect the electronic transmission behavior of the material and increase the volume resistivity of the material to a certain extent; if rare earth oxides are not added, the electronic transmission characteristics of the material may change, and the carrier concentration or mobility will increase, resulting in a decrease in volume resistivity.

[0089] No silicon powder is added to the colloidal material of Comparative Example 4. Compared with Example 1, Comparative Example 4 is inferior to Example 1 in terms of glass liquid erosion rate, thermal expansion coefficient and volume resistivity. This is because silicon powder can improve the compactness of castable refractory materials, fill the pores and microcracks in the material, make the material structure more compact, and reduce the channels for glass liquid to penetrate into the material. Silicon powder has a lower thermal expansion coefficient and can play a role in regulating thermal expansion in the material. When the material is heated, silicon powder can limit the thermal expansion of the matrix material and reduce the overall thermal expansion coefficient of the material. Silicon powder also has good insulation and can improve the volume resistivity of the material. The uniform distribution of silicon powder can form an insulating network to hinder the conduction of current.

[0090] Boric acid is not added to the colloidal material of Comparative Example 5. Compared with Example 1, although Comparative Example 5 is superior to Example 1 in terms of glass liquid erosion rate, thermal expansion coefficient and volume resistivity, the addition of boric acid is mainly used as a flux and binder to adjust the fluidity of the material, so that the mixture forms a colloidal substance after heating, which is convenient for use, and can also promote the rapid solidification of the material at high temperature and close bonding with the base material. When boric acid is not added, the material is difficult to form a colloidal substance, which is not convenient for use.

Claims

1. Colloid material for hot repair of high zirconium bricks in electronic glass furnace, characterized in that: The invention comprises the following components in percentage by mass: 50-70% of zirconium dioxide, 10-20% of single crystal powdered aluminum oxide, 5-15% of silicon micropowder, 2-8% of boron compound, 1-4% of rare earth oxide, 0-3% of silicon carbide, 0-5% of nano aluminum oxide and 5-15% of phosphate binder.

2. The colloidal material for hot repair of high zirconium bricks for electronic glass furnace according to claim 1, characterized in that: The boron compound is boric acid or boron oxide.

3. The colloidal material for hot repair of high-zirconium bricks for electronic glass furnaces according to claim 1, characterized in that: The rare earth oxide is yttrium oxide.

4. The colloidal material for hot repair of high zirconium bricks for electronic glass furnace according to claim 1, characterized in that: The phosphate binder is magnesium dihydrogen phosphate.

5. The method for preparing the colloidal material for hot repairing of high zirconium bricks for electronic glass furnaces according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1 raw material pretreatment; S2 mixes the raw materials uniformly to obtain a mixed material; S3 heats the mixture to obtain a gelatinous material.

6. The method for preparing the colloidal material for hot repairing of high-zirconium bricks for electronic glass furnaces according to claim 5, characterized in that: In step S1, the specific operation of raw material pretreatment is: grinding each raw material except nano-alumina separately, and screening through a sieve.

7. The method for preparing the colloidal material for hot repairing of high-zirconium bricks for electronic glass furnaces according to claim 6, characterized in that: In step S1, the particle sizes of the raw materials after screening are 100-300 mesh of zirconium dioxide, 200-400 mesh of single crystal powdered alumina, 300-500 mesh of silicon powder, 200-300 mesh of boron compound, 150-300 mesh of rare earth oxide, 150-300 mesh of silicon carbide, and 200-300 mesh of phosphate binder.

8. The method for preparing the colloidal material for hot repairing of high-zirconium bricks for electronic glass furnaces according to claim 5, characterized in that: In step S2, the raw materials except the phosphate binder are mixed and the phosphate binder is added during the mixing process, and stirred until a uniform mixture is formed.

9. The method for preparing the colloidal material for hot repairing of high-zirconium bricks for electronic glass furnaces according to claim 5, characterized in that: In step S3, the mixed material is heated at 200-500° C. until it forms a gelatinous material.

Citation Information

Patent Citations

  • High temperature resistant inorganic composite adhesive

    CN101426872A

  • Lining repairing material for kiln

    CN117865666A

  • Refractory material for glass kiln as well as preparation method and application of refractory material

    CN118324485A

  • Powdery repairing agent for hearth of coke oven carbonization chamber and method for repairing

    JP2007145890A